Accuracy analysis of Bluetooth-Low-Energy ranging and positioning in NLOS environment. (1st October 2020) - Yang, Deng; Wang, Jian; Wang, Minmin; Han, Houzeng; Zhang, Yalei
ABSTRACT: Aiming at the low accuracy of Bluetooth-Low-Energy ranging and positioning in NLOS environment, a non-line of sight (NLOS) Bluetooth-Low-Energy ranging method based on the NLOS Bluetooth-Low-Energy ranging model and an NLOS Bluetooth-Low-Energy positioning algorithm based on the TLS method and the triangular positioning algorithm are proposed. Firstly, an line-of-sight (LOS) Bluetooth-Low-Energy ranging model is established by RSSI value and actual distance between the Bluetooth-Low-Energy beacon and the terminal equipment. Secondly, based on the LOS Bluetooth-Low-Energy ranging model and the threshold-corrected RSSI peak, an NLOS Bluetooth-Low-Energy ranging model is established. Thirdly, the NLOS RSSI value is processed by the NLOS Bluetooth-Low-Energy ranging model to obtain the optimal ranging value. Finally, high precision positioning coordinates can be obtained by using NLOS Bluetooth-Low-Energy positioning algorithm and optimal Bluetooth-Low-Energy ranging. In this paper, two experiments are carried out, and the experimental results show that: in the range of 7 m, the average ranging accuracy of the improved NLOS Bluetooth-Low-Energy ranging method is 0.37 m, which is improved 49.19% when compared to the traditional method's results. The average positioning accuracy is 0.4 m using the positioning algorithm proposed in this paper. Therefore, in NLOS environment, the proposed ranging method and positioning algorithm can significantly improve the accuracy of Bluetooth-Low-Energy ranging and positioning.